(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: Deceased donor kidney transplantation is a crucial alternative for patients with end-stage renal disease lacking living donors. This study aimed to characterize the morphofunctional parameters of post-mortem renal allograft (RA ex-mortuo) transplantation when modeling super-rapid recovery and delayed recovery for two types of asystole donors. Materials and Methods: The study assessed the morphological and histochemical parameters of RA ex-mortuo under ex vivo conditions in 39 dogs. The morphological analysis involved kidney biopsies and perfusate examination using light microscopy, morphometric studies, and histostereometric analysis. The study evaluated the height of the renal epithelium in the proximal and distal tubules, the specific volume of glomeruli in the cortex, and the prevalence of dystrophic changes in the tubular epithelium. Lipid peroxidation products in the perfusate were analyzed, and tissue enzyme activity was measured. The study proposed an evaluation algorithm and corresponding criteria to characterize the resource potential of delayed recovery. The effectiveness of RA rehabilitation ex-mortuo was evaluated using a scale based on morphological and metabolic disorder severity. Results: The study pioneered the multicriteria principle to classify asystolic donors as super rapid and delayed recovery, enhancing the understanding of theoretical and practical integration in simulated reality. Using non-perfusion hypothermia ex vivo for rehabilitating RA ex-mortuo requires 60 min to lower basal metabolism, as indicated by reduced succinate dehydrogenase and phenoloxidase activity. Early rehabilitation stages showed decreased metabolism, with enzyme activity significantly decreasing at 30 min. Metabolic disorders were satisfactory at 35 points and mild to severe at 16 points. Conclusion: The activity of key enzymes during ex-mortuo RA rehabilitation showed reduced metabolic processes in both models. Indicators such as AR (−0.09) and AF (0.001%) suggest positive rehabilitation outcomes at both 30 and 120 min, which are closely linked to the temporal risk factor.